Fault location of single-phase grounding fault based on Manhattan average distance and cosine similarity in distribution network - TAO Weiqing; LI Xueting; HUA Yuting; XIAO Songqing; WU Yan; ZHANG Yingjie (电力工程技术, 2023)
Aiming at the problem of insufficient sensitivity of existing fault location methods when single-phase grounding fault occurs in resonant grounding system of active distribution network, a fault location algorithm based on Manhattan average distance and cosine similarity is proposed. Firstly, the neutral point grounding method of distributed generator (DG) is defined and the influence of DG access is analyzed. Secondly, the transient zero-sequence current at both ends of each section of the fault feeder is decomposed by wavelet packet. Then the amplitude similarity is calculated by Manhattan average distance, and the waveform difference is compared based on cosine similarity. As a result, a comprehensive similarity criterion is constructed, and the fault section can be distinguished by comparing with the set threshold. Finally, the simulation model is built in DIgSILENT PowerFactory. Simulation result shows that the proposed method can locate faults accurately under different fault locations, different fault moments and different transition resistances.